Sweden : Selected Issues. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2014)
This Selected Issues Paper on Sweden focuses on macroprudential policies in Sweden. Sweden's banking system meets most standard measures of financial soundness. However, with its large and wholesale-dependent banking sector, high and increasing household debt, and resurgent house price growth, additional measures are needed to contain mounting financial stability risks. On the supply side, this means continuing to strengthen capital and liquidity requirements. However, theoretical and empirical evidence points to a need to also limit credit demand, including through effective steps to increase the rate of mortgage amortization. Empirical evidence suggests that demand-side measures are effective in curbing household borrowing. There is less evidence on the simultaneous use of these tools-a scenario particularly relevant for Sweden. The model also suggests that higher policy rates will impact both mortgage supply and demand. The main findings are qualitatively unchanged across different sample periods and alternative sign restrictions-for example, about the contemporaneous correlation between the monetary policy shock and output and inflation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet